AB0579 Autoimmune Cytopenia in Primary Sjogren's Syndrome is Associated with Severe Ocular Surface Damage, Tear Film Instability, and Less Articular Involvement. (9th June 2015) - Koh, J.H.; Lee, J.; Jung, S.-M.; Min, H.K.; Kim, J.H.; Jeon, H.; Kwok, S.-K.; Park, S.-H.
Abstract : Background: Autoimmune cytopenia is one of the common exrtaglandular manifestations (EGMs) of pSS. However, only a few studies have been conducted on hematologic abnormalities and their significance in pSS, and cytopenia is often disregarded in daily practice with pSS patients, as the degree of cytopenia is usually mild and asymptomatic. Objectives: We investigated the prevalence of EGMs among participants in the Korean Initiative of primary Sjogren's syndrome (KISS) cohort, according to European League Against Rheumatism (EULAR) Sjogren's syndrome disease activity index (ESSDAI) domains. The EULAR task force on Sjogren's syndrome (SS) recently developed the ESSDAI, which includes all possible EGMs and their definitions. In addition, we investigated cytopenia, the common manifestations of pSS, and their correlation with various phenotypic features of pSS. Methods: We analyzed 113 participants from the KISS, a prospective pSS cohort. Autoimmune cytopenia was defined as autoimmune origin neutropenia, anemia, and/or thrombocytopenia without vitamin or iron deficiency or drug-induced cytopenia. To identify the association between autoimmune cytopenia and clinical characteristics of pSS, extraglandular manifestations were analyzed according to the ESSDAI definition. Xerophthalmia was assessed with the Ocular Surface Disease Index, Schirmer I test, ocular stain score (OSS), tear film break up time (TBUT). Results: The median total ESSDAI score was 2 (IQR 0.5–6). About a quarter of patients had no systemic activity. Autoimmune cytopenia was observed in 23.9% of patients (n=27). Moderate biological features were more frequently observed in patients with autoimmune cytopenia than in patients without [10 (37%) and 11 (12.8%), respectively, p =0.016]. Articular involvement was exhibited in one patient with autoimmune cytopenia, but in 22 patients (26.5%) without autoimmune cytopenia ( p =0.039). Higher OSS ( p =0.003 using SICCA method, p =0.019 using van Bijsterveld's scoring system) and lower mean Schirmer I test ( p =0.029) were observed in patients with autoimmune cytopenia than in those without. Leukocyte counts correlated with OSS by both methods (van Bijsterveld's, r =-0.216 [ p =0.045]; SICCA, r =-0.265 [ p =0.007]) and TBUT ( r =0.241 [ p =0.019]). Conclusions: Autoimmune cytopenia is closely associated with severe ocular surface damage in pSS. Therefore, assessment of xerophthalmia by ophthalmologists may be mandatory, particularly in pSS patients with cytopenia, even if patients do not complain of eye dryness. References: Fox RI. Sjögren's syndrome. Lancet 2005;366:321-31. Seror R, Ravaud P, Bowman SJ, Baron G, Tzioufas A, Theander E, et al. EULAR Sjogren's syndrome disease activity index: development of a consensus systemic disease activity index for primary Sjogren's syndrome. Ann Rheum Dis 2010;69:1103-9. Hernandez-Molina G, Michel-Peregrina M, Bermúdez-Bermejo P, Sánchez-Guerrero J. Early and late extraglandular manifestations in primary Sjögren's syndrome. Clin Exp Rheumatol 2012;30:455. Acknowledgements: Supported by a grant from the Korean Health Technology R&D Project, Ministry of Health & Welfare, Republic of Korea (HI13C0016). Disclosure of Interest: None declared